Traction force microscopy for linear and nonlinear elastic materials as a parameter identification inverse problem - Sarnighausen, Gesa; Thi Ngoc Nguyen, Tram; Hohage, Thorsten; Sinha, Mangalika; Köster, Sarah; Betz, Timo; Schwarz, Ulrich S.; Wald, Anne (Inverse problems, 2025)
Traction force microscopy (TFM) is a method widely used in biophysics and cell biology to determine forces that biological cells apply to their environment. In the experiment, the cells adhere to a soft elastic substrate, which is then deformed in response to cellular traction forces. The inverse problem consists in computing the traction stress applied by the cell from microscopy measurements of the substrate deformations. In this work, we consider a linear model, in which 3D forces are applied at a 2D interface, called 2.5D TFM, and a nonlinear pure 2D model, from which we directly obtain a linear pure 2D model. All models lead to a linear resp. nonlinear parameter identification problem for a boundary value problem of elasticity. We analyze the respective forward operators and conclude with some numerical experiments for simulated and experimental data.